Forage production and crude protein content of perennial warm-season grasses under fertilization (Semiárida, 2020)
The essay was carried out to determine the effect of defoliation frequency on yields, dry matter composition and protein content in three Old World bluestems cultivars (Bothriochloa sp cv. Dahl, Spar, Plains) and one of sideoats grama (Bouteloua curtipendula (Mich.) Torrey cv. Vaughn) on the growth season. Defoliation (4 frequencies) and participants were arranged within a split plot design. Yields of whole plant dry matter (WPY) and blade (LY) -kg.ha-1.y-1, crude protein content In L (CP, %), yield of CP of L (CPY, kg.ha-1.y-1) and mean values of growth rate (gr, kgDM.ha-1.d-1) for WP and L were measured. Data were analyzed by proc GLM (SAS) and means were compared by Tukey test (p
Keywords: forage grasses; defoliation; forage production; crude protein; quality